Study on Soil Properties Towards Formation of High-Quality Agarwood Resin in Aquilaria Crassna - Mohd Syafik, Mohamad Hamdan; Mohd Azrul Hisham, Ismail; Siti Hajar Noor, Shaarani; Saiful Nizam, Tajuddin (Trans Tech Publications, 2021)
Agarwood has been used for its fragrance and medicinal properties in Asian culture for centuries. In recent years, agarwood gains its popularity in the west due to its usage in perfume formulation. Unfortunately, the supply does not meet the augmentation market demand. This is mostly because of depleting nature agarwood reservoir and lack of induction technique that can produce agarwood consistently in the plantation. In this study, we look into a case where artificial inducing technique successfully produced high quality agarwood. To assure its quality, agarwood chip was analysed by Gas Chromatography for its chemical profiles. Discovered compounds were identified as sesquiterpene group which also had been characterized as major agarwood compound listed on previous studies. Few compounds that are detected such as δ-cadinene (0.20%), jinkoh-eremol (22.09%), epi-α-cadinol (4.74%), agarospirol (3.75%) and others. Soil condition that contributes into this agarwood formation; soil analysis on physical properties, chemical properties and nutrients content of the soil have been analyzed. Based on the findings, soil condition is an important factor to successfully induced high quality agarwood.